Consumer preferences for on-demand transport in Australia. (February 2020) - Vij, Akshay; Ryan, Stacey; Sampson, Spring; Harris, Susan
Abstract: On-demand transport (ODT) refers to adaptive transport services that use a fleet of vehicles to provide shared flexible transport to consumers, when and where they need it. This study surveyed 3, 985 geographically and demographically representative Australians nationwide, to understand consumer demand and willingness to pay for ODT in Australia. Our analysis finds that the current market for ODT services in Australia is small. For example, for an ODT service that costs roughly the same as UberX's ridesharing service, and offers comparable level-of-service, our analysis predicts that only 17 per cent of the Australian population can be expected to use the service a few times a week or more. However, shared electric autonomous vehicles could significantly change the business case for ODT services, by enabling on-demand door-to-door transport services at a fractional cost of similar existing services. Our analysis finds that while consumers are willing to pay, on average, 0.28$/km more to avoid sharing a vehicle with other passengers, 0.17$/km more for door-to-door service, and 0.10$/km to be able to book the service in real time, cost is the most important determinant of ODT use (of the service attributes included in our analysis). For an ODT service that provides the same level-of-service as UberX, but at a fractional cost of $0.30 per km, 31 per cent of the Australian population can be expected to use the service a few times a week or more. And this figure is likely to be larger once we account for more long-term changes in lifestyles that might accompany the introduction of these services. We find that frequency of ODT use is strongly correlated with age and lifecycle stage: young individuals who are employed full-time are likely to use ODT most frequently; older adults who have retired from the workforce and whose children have left home are likely to be infrequent users. Overall, our analysis indicates that ODT services have the ability to both increase public transport use among existing public transport customers, and to draw new customers to public transport services.